Improving Students' Digital Literacy through the Physics Simulation Interactive Carnot-Sim Application (PhySIC-SIM) - Ana Silfiani Rahmawati; Ida Hamidah; Achmad Samsudin; Diana Rochintaniawati (Borneo Research and Education Center, 2026)
This study aims to analyze the effect of using the PhySIC-SIM interactive simulation application on improving the digital literacy of prospective physics teacher students in learning the Carnot cycle. This study used a quasi-experimental method with a single-group pretest-posttest design involving 19 students enrolled in a thermodynamics course. The instrument used was a digital literacy test based on nine indicators, including understanding basic concepts, unit operation configuration, creativity optimization, revision management, communication of results, database selection, and validity evaluation. Data were analyzed using descriptive statistics, the N-Gain test, a paired sample t-test, and effect size analysis (Cohen's d). The results showed that the average student score increased from 13.11 (52.44%) in the pretest to 21.63 (87%) in the posttest. The average N-Gain value of 0.71 indicates a high improvement category. Furthermore, the paired sample t-test revealed a significance value of p < 0.05, indicating a significant difference between the pretest and posttest scores. The effect size calculation yielded a Cohen's d value of 3.16, indicating a very large effect. This finding suggests that PhysIC-SIM effectively improves students' digital literacy. Nevertheless, this study is limited by the use of a one-group pretest-posttest design without a control group and the relatively small sample size, which may limit the generalizability of the findings. Therefore, future studies are recommended to involve larger samples and experimental comparison groups to obtain more comprehensive evidence regarding the effectiveness of PhySIC-SIM.